Brand strategies in social media in hospitality and tourism - Moro, S. (2018)
Purpose This study presents an automated literature analysis to unveil the drivers for incorporating social media in tourism and hospitality brand strategies. Design/methodology/approach To gather relevant literature, Google Scholar was queried with “brand”/“branding” AND “social media” for articles in ten top ranked tourism and hospitality journals, resulting in a total of 479 collected articles. The methodology adopted for the analysis is based on text mining and topic modeling procedures. The topics discovered are characterized by terms belonging to a dictionary previously compiled and provide a segmentation of the articles in coherent sets of the literature. Findings Most of the 213 articles that encompass a strong relation between social media and branding are mentioning mainly brand building stages. A large research gap was found in hospitality and tourism considering that, besides advertising, no topic was discovered related to known brand strategies such as co-branding or franchising. Practical implications The present analysis concludes that specialized tourism and hospitality literature needs to keep pace with research that is being conducted on a wide range of industries to assess the influence of social media. Originality/value The automated analysis approach used has no precedent in tourism and hospitality research. By including an innovative topical concept map, it led to identifying and summarizing the topics, providing a clear picture on the findings. This study calls for research by specialized tourism and hospitality publications, eventually leading to special issues on this vibrant subject.